Perjanjian Pasca-Nikah (Postnuptial Agreement) dalam Konteks Maqashid al-Syari’ah: Analisis Pandangan al-Syatibi - Mohammad Rafli; Fahmi Muhaemin Zaen; Sya’bana, Bambang Ari (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Purpose – The aim of this research is to delve into and elucidate the concept of post-marital (postnuptial agreement.) agreements within the framework of the Maqashid al-Syari'ah, particularly through the lens introduced by al-Syatibi. Methods – The research methodology employs a Library Research approach grounded in the perspective of Maqashid al-Syari'ah as articulated by al-Syatibi, centering on descriptive analysis. This process entails systematic exploration and examination of literature and pertinent sources to grasp the nuances of Maqashid al-Syari'ah concepts as elucidated by al-Syatibi, while providing comprehensive insights into the intricacies of post-marital agreements within this framework. Findings – The study reveals that post-marital agreements play a crucial role in managing marital assets, especially in polygamous marriages, while prioritizing family welfare. Through the lens of Maqashid al-Shari'ah, marriage contracts ensure various benefits: preserving religious values, safeguarding against health risks, protecting children from psychological trauma, ensuring offspring welfare and rights, and safeguarding property rights, particularly in polygamous unions, thus enhancing economic stability within families. Research implications – The theoretical implications underscore the crucial role of maqashid al-Shari'ah in shaping post-marital agreements and Islamic marriage contracts. They stress that concepts like Hifz al Din, Hifz al Nafs, Hifz al 'Aql, Hifz al Nasl, and Hifz al Mal are pivotal in ensuring these agreements reflect Islamic values and offer optimal protection for all involved. Moreover, they prompt further exploration of the interplay between Islamic law, maqashid al-Shari'ah, and marital practices, enhancing theoretical understanding and informing legal policies in Muslim societies. Originality/value – In sum, the study underscores the profound implications of post-marital agreements and marriage contracts within the framework of maqashid al-Shari'ah, underscoring their role in fostering familial harmony, protecting individual rights, and upholding Islamic principles of justice and equity.